A Preliminary Study on Optimizing the In-Lab Reclamation Process Parameters of Used Transformer Oils Using the Taguchi Method - Sharin Ab Ghani; Zulkarnain Ahmad Noorden; Nor Asiah Muhamad; Imran Sutan Chairul; Muhammad Asyraf Mohd Khalid (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this study, the Taguchi method is used to optimize the in-lab reclamation process parameters of used transformer oils. The main benefit of this method is that one can determine the optimum parameters of the reclamation process in a simple, efficient, and cost-effective manner. The L4 (23) Taguchi design is used to optimize the following process parameters: (1) weight of the Fuller’s Earth adsorbent, (2) stirring speed, and (3) oil temperature. These parameters are optimized in order to minimize the AC breakdown voltage, total acid number, and dynamic viscosity of the reclaimed transformer oil samples. The signal-to-noise ratios are determined for each process parameter in order to identify the significance of each factor on the three output responses. Based on the results, the oil temperature has the most significant effect on the AC breakdown voltage whereas the weight of the Fuller’s Earth adsorbent has the most significant effect on the total acid number and dynamic viscosity of the reclaimed transformer oils. Tests are carried out to verify the results using the optimum reclamation process parameters and indeed, it is found that there is significant improvement in the mean AC breakdown voltage, total acid number, and dynamic viscosity for the reclaimed transformer oil compared with those for the used transformer oil. It is believed that this method can be an indispendable tool to determine the optimum parameters for the reclamation process without going through the hassle of trial and error associated with conventional experimentation.